2005
DOI: 10.1111/j.1471-4159.2004.03007.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple pathways of apolipoprotein E signaling in primary neurons

Abstract: Apolipoprotein E is a genetic risk factor for Alzheimer's disease, and the apoE protein is associated with b-amyloid deposits in Alzheimer's disease brain. We examined signaling pathways stimulated by apoE in primary neurons in culture. ApoE and an apoE-derived peptide activated several intracellular kinases, including prominently extracellular signalregulated kinase 1/2 (ERK1/2). ERK1/2 activation by apoE was blocked by an inhibitor of the low-density lipoprotein receptor family, the specific NMDA glutamate r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
112
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 107 publications
(117 citation statements)
references
References 48 publications
(123 reference statements)
4
112
0
1
Order By: Relevance
“…Activation of the AKT and ERK pathways was through the LRP1 receptor (83). A tandem repeat ApoE mimetic peptide also induced phosphorylation of Dab-1 independent of effects on ERK and AKT signaling (84). ApoE signaling may also inhibit normal Reelin signaling (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of the AKT and ERK pathways was through the LRP1 receptor (83). A tandem repeat ApoE mimetic peptide also induced phosphorylation of Dab-1 independent of effects on ERK and AKT signaling (84). ApoE signaling may also inhibit normal Reelin signaling (19).…”
Section: Discussionmentioning
confidence: 99%
“…ApoE induces phosphorylation of the AKT and ERK pathways and inhibition of the JNK pathway (83)(84)(85). Activation of the AKT and ERK pathways was through the LRP1 receptor (83).…”
Section: Discussionmentioning
confidence: 99%
“…Studies from several groups have demonstrated that apoE receptors affect kinase signaling cascades by affecting calcium influx (5,7,24,26). Another study showed a direct effect of apoE receptors on calcium influx via NMDA receptors (4).…”
Section: Discussionmentioning
confidence: 99%
“…Data were analyzed using analysis of variance with Graphpad Prism 4 software, using Tukey's Multiple Comparison test for post-hoc analyses with significance determined as p Ͻ 0.05. cellular kinase activation, including activating extracellular signal-regulated kinase 1/2 (ERK 1/2) (7). ERK 1/2 activation required active NMDA receptors and calcium influx, suggesting that some apoE receptors interact with NMDA receptors (7). To test whether ApoEr2 directly interacted with the NMDA receptor, we transfected COS7 cells with ApoEr2 and NR1, immunoprecipitated NR1, and probed the precipitates with anti-HA.…”
Section: Methodsmentioning
confidence: 99%
“…The lipoprotein receptors ApoER2 and VLDLR can activate pro-survival signaling through the inactivation of the JNK-pathway and by increasing PI3K and ERK1/2 activity [29]. Proprotein convertase subtilisin/kexin type 9 has the ability to bind and degrade ApoER2 and VLDLR [7].…”
Section: Cells Protected By Pcsk9 Rnai Exhibit Altered Levels Of Lipomentioning
confidence: 99%